ANALYSIS OF ABILITY DIGITAL LITERACY FOR LIBRARIANS AT SURABAYA STATE UNIVERSITY LIBRARY - Najwa Wahyu Aqila; Bakhtiyar; Bambang Prakoso (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
Development technology very rapid information has change face library become center service digital information. Librarian No Again only on duty in service physical , but also required For own ability digital literacy which includes access , evaluation , creation , reflection , and participation information in a way critical and ethical research​ This done For know to what extent is the ability digital literacy of librarians at the UPT Library of Surabaya State University (UNESA), with use five element theory digital literacy from Renee Hobbs (2010), namely access, analyze, create, reflect, and act. Research This use approach qualitative descriptive. Data collection techniques are carried out through interview deep against five librarians from various field services, namely collection work scientific, references and publications periodically, two of circulation, as well as automation and conservation. Data analysis was performed using the Miles, Huberman, and Saldaña model which includes stage data reduction, data presentation, and data extraction conclusion. Research results show that ability librarian in access and analyze aspects are in the category good, but the ability in the aspects of create, reflect, and act is still diverse and yet evenly. Some librarian Not yet active make digital content, not yet in a way consistent reflect mark ethical in management information, and minimal involvement in public digital spaces. It is necessary training digital literacy in general comprehensive, collaborative between divisions, as well as support policy institutional so that librarians can play a role as agent digital literacy in environment academic.